If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x^98+17*x^95+x^2-3*x+1;x^2+1
(2*x-1)/2-(4/3) = 10/3-((x+1)/3);x
x
1;3;1;2;0;0
x^98+17*x^95+x^2-3*x+1;x^2+1
x^2 = 3*x-2;x
x
| 56x=986 | | 0.7+s=8.2 | | 6.44x+81=41.4736+9x | | 4=-2h+-4 | | -(-2)+(3)(3)= | | 3(-7+7x)=42 | | -7(8+x)=-105 | | -3(-3-x)=24 | | -7(2t+1)=7 | | 7(9-7x)=504 | | 5p+15=5p+15 | | 5p+15=5p-15 | | 7(-2x+9)=-21 | | 6u+15=33 | | 4a+5(a-3)= | | -3(-1x+4)=9 | | 18b^2+45b+8=-17 | | -10(s+2)=-49 | | x=5-((1*(3/2))/3) | | 2k-6=4k+6 | | 2+2q=12 | | 4p+3=4p+12 | | 4-3b=13 | | 7x-1=-6x+12 | | -30+3x=24 | | -5+7x=37 | | 103-w=167 | | 5*5-4X=6 | | -2=2p+4 | | logx=3/2 | | -4x+3=6x-97 | | -14=5u-4 |